The 2019 Cervical Spine Research Society (CSRS) Asia Pacific Traveling Fellowship. Issue 10 (December 2020) - Aleem, Ilyas; Tan, Lee; Bosco, Aju; Reinas, Rui; ter Wengel, Paula V.; Dennis Hey, Hwee Weng
Abstract : The Cervical Spine Research Society (CSRS) is dedicated to advancing the care of patients with cervical spine pathology. The authors present here highlights of the 2019 CSRS-Asia Pacific Traveling Fellowship.